Annual Housing Survey, 1980 (United States): National Core File ([Verlag nicht ermittelbar], 1984)
This data collection provides information on the characteristics of a national sample of housing units. Data include the year the structure was built, types and number of living quarters, presence of a garage, occupancy status, access, number of rooms and bedrooms, presence of commercial establishments on the property, and property value. Additional data focus on kitchen and plumbing facilities, types of heating fuel used, source of water, sewage disposal, and heating and air conditioning equipment. Information provided on housing expenses includes monthly mortgage or rent payments, cost of services such as utilities, garbage collection, and property insurance, and amount of real estate taxes paid in the previous year. Indicators of housing quality are also supplied, including presence of cracks or holes in walls, ceilings, or floors. In addition to housing characteristics, demographic data are provided on household members, such as age, sex, race, marital status, income, and relationship to household head. Additional data are provided for household head, including Hispanic origin, length of residence, and years of school completed.